Correlation of serum antigen and antibody concentration with clinical features in HIV infection. Issue 2 (February 1991) - Ellaurie, M; Rubinstein, A
Abstract : Serum antigen and antibody values were studied in 164 infants and children infected perinatally with HIV. HIV antigens p17, p24, gp41, and gp120 were determined in sera by immunoblot and antigen capture assays. Lymphocyte blast transformation, serum immunoglobulins, and circulating immune complexes were also evaluated. Altogether 50 patients had HIV antigens measured: 31 (62%) patients had p17 antigen in the serum and 29 (58%) had p24 antigen present. In 19 (38%) and nine (18%) patients, respectively, gp120 and gp41 were detected. All four HIV antigens were detected in seven (14%) patients. There was a positive correlation between the concentration of each HIV sequential specimens were outcome. When sequential specimens were analysed, 120 (73%) patients had p24 antigen present. Patients with stage P2B and P2D (Centers for Disease Control classification) had the highest concentrations of p24 antigen with a mean of approximately 200 pg/ml. Altogether 70% of patients with a p24 antigen concentration of greater than 30 pg/ml eventually died or had severe clinical disease within six to 24 months. Infants under 15 months of age with a p24 antigen concentration as low as 5 pg/ml also did poorly. Increased immunoglobulins and decreases in mitogenic responses and absolute CD4+ lymphocyte counts were more prevalent in patients with raised p24 antigen. Raised concentrations of circulating immune complexes were seen in the symptomatic phase of the disease whereas in the terminal stage of the disease raised serum antigen and a decrease in circulating immune complexes and absolute CD4+ lymphocyte count were evident. Loss of p24 and/or p17 antibody as well as a decreasing ELISA optical density for HIV antibody also signalled progression of the disease.